2017
DOI: 10.1126/science.aai8801
|View full text |Cite
|
Sign up to set email alerts
|

Multicluster Pcdh diversity is required for mouse olfactory neural circuit assembly

Abstract: The vertebrate clustered protocadherin (Pcdh) cell surface proteins are encoded by three closely linked gene clusters (Pcdhα, Pcdhβ, and Pcdhγ). Here, we show that all three gene clusters functionally cooperate to provide individual mouse olfactory sensory neurons (OSNs) with the cell surface diversity required for their assembly into distinct glomeruli in the olfactory bulb. Although deletion of individual Pcdh clusters had subtle phenotypic consequences, the loss of all three clusters (tricluster deletion) l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
181
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 148 publications
(201 citation statements)
references
References 33 publications
10
181
0
Order By: Relevance
“…The neuronal self-avoidance and tiling functions are consistent with Pcdhs initiating repulsion [24], while Pcdhs also play other roles such as promoting the complexity of a neuron’s dendritic arbor [44]. We note that although this review focuses on the role of Pcdhs in neuronal self-avoidance in promoting repulsion, the cis and trans interactions formed between Pcdhs that we have described here are also relevant to the adhesive functions of Pcdhs.…”
Section: Two Models Of the Pcdh Recognition Complex And Associatedmentioning
confidence: 69%
See 3 more Smart Citations
“…The neuronal self-avoidance and tiling functions are consistent with Pcdhs initiating repulsion [24], while Pcdhs also play other roles such as promoting the complexity of a neuron’s dendritic arbor [44]. We note that although this review focuses on the role of Pcdhs in neuronal self-avoidance in promoting repulsion, the cis and trans interactions formed between Pcdhs that we have described here are also relevant to the adhesive functions of Pcdhs.…”
Section: Two Models Of the Pcdh Recognition Complex And Associatedmentioning
confidence: 69%
“…For example, recent studies have shown that unique interaction of PcdhγC3 with Axin1 inhibits Wnt signaling [70]. In general, a more complex picture of Pcdh gene expression is emerging, in which distinct Pcdh gene clusters are expressed in different types of neurons, and the alternate and C-type isoforms are differentially expressed during the development of neural circuits [4, 16, 60]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Whereas mature serotonergic neurons predominately express Pcdh α c2 (and Pcdh γ c3 and Pcdh γ c4 at lower levels) but not the alternate Pcdh isoforms, mature olfactory sensory neurons (OSNs) predominantly express alternate isoforms but not C-type isoforms (28). These cell type–specific patterns of expression correlate with the distinct axonal-arborization patterns of the two types of neurons.…”
Section: Discussionmentioning
confidence: 99%